2021
DOI: 10.1002/fsn3.2355
|View full text |Cite
|
Sign up to set email alerts
|

Effect of slurry ice during storage on myofibrillar protein of Pseudosciaena crocea

Abstract: In order to explore the effect of slurry ice on myofibrillar protein of Pseudosciaena crocea, the changes in myofibrillar protein and muscle microstructure during storage were studied with crushed ice as a control. During the storage period, the rate of decrease in myofibrillar protein content, Ca2+‐ATPase activity, and total sulfhydryl groups in the slurry ice group was lower than in the control group (p < .05). There was a significant linear correlation between the hydrophobicity and the storage time (Rcrush… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Traditional ice storage is simple to operate, no power demand and can maintain the biological characteristics of aquatic products, but rough surface and poor fluidity can cause surface friction damage. Several researchers have manifested that slurry ice could significantly solve these problems 4–7 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional ice storage is simple to operate, no power demand and can maintain the biological characteristics of aquatic products, but rough surface and poor fluidity can cause surface friction damage. Several researchers have manifested that slurry ice could significantly solve these problems 4–7 …”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have manifested that slurry ice could significantly solve these problems. [4][5][6][7] Slurry ice is a homogeneous two-phases aqueous secondary refrigerant consisting of tiny ice particles and a carried liquid. Slurry ice can reduce damage caused by surface abrasion, slow down the chemical and enzymatic reactions, allow a faster cooling and wash surface, which primarily results from its physical and engineering properties, such as tiny and smooth ice particles, great refrigeration and flow property, and high heat exchange rate.…”
Section: Introductionmentioning
confidence: 99%
“…A gradual decline in the myofibrillar protein along with an upsurge in denatured protein was observed with the progress of post-mortem storage time. Feng et al also reported that in Pseudosciaena crocea, the myofibrillar protein was decreases with increase in storage time in slurry ice (25) . Total collagen in the fish muscle declined from 1.12% to 0.36% during the storage period.…”
Section: Protein Fractionsmentioning
confidence: 92%